2002
DOI: 10.1088/0953-8984/14/12/321
|View full text |Cite
|
Sign up to set email alerts
|

Testing interaction models by using x-ray absorption spectroscopy: solid Pb

Abstract: Structural models obtained using classical molecular dynamics (MD) simulations and realistic interatomic potentials for solid metals are tested using experimental results obtained by x-ray absorption spectroscopy (XAS). Accurate L-edge extended x-ray absorption fine-structure (EXAFS) measurements of Pb grains dispersed in BN and graphite matrices have been collected for temperatures up to the melting point. The thermal expansion of the grains was measured by energy-dispersive x-ray diffraction techniques and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 44 publications
(85 reference statements)
1
31
0
Order By: Relevance
“…[15]). Structural refinement was aimed only to obtain accurate measurements of the variation of the cell parameters a (Ge I), or a and c (Ge II and III) under high pressure and high temperature conditions, which determine the energy position of the Bragg reflections hkl associated with a given interplanar distance d, for fixed diffraction angle q E ¼ hc 2d sin ðqÞ .…”
Section: Data-analysismentioning
confidence: 99%
“…[15]). Structural refinement was aimed only to obtain accurate measurements of the variation of the cell parameters a (Ge I), or a and c (Ge II and III) under high pressure and high temperature conditions, which determine the energy position of the Bragg reflections hkl associated with a given interplanar distance d, for fixed diffraction angle q E ¼ hc 2d sin ðqÞ .…”
Section: Data-analysismentioning
confidence: 99%
“…We have shown in [10] that the DLE interaction model reproduces the structure of solid Pb poorly. At the same time, the EA is a many-body potential designed to reproduce the specific long-range solid state properties of Pb.…”
Section: Xas Analysis Results and Discussionmentioning
confidence: 98%
“…At the same time, the EA is a many-body potential designed to reproduce the specific long-range solid state properties of Pb. It has been shown in [10] to produce structural models excellently compitable with EXAFS-extracted data for solid lead. In the present work we have shown that this EA model is unable to reproduce the shape of g(r) in liquid Pb.…”
Section: Xas Analysis Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations